Natural Hydroxyapatite Extracted From Bovine Bone - Bano, Nazia; Jikan, Suzi Salwah; Basri, Hatijah; Abu Bakar, Sharifah Adzila; Nuhu, Awwal Hussain (Journal of Science and Technology, 2017)
The aim of this study is to extract natural hydroxyapatite (HAP) from bovine bone. Hydrothermal method followed by calcination treatment at different temperatures is used in this current research. Bovine bone has potential for producing hydroxyapatite, a chief component present in bone and teeth of vertebrates. HAP is an excellent material used in bone restoration and tissue regeneration. Characterizations of the bovine bone natural HAP powder were done by scanning electron microscopy (SEM), Fourier transforms infrared (FTIR) and energy dispersive x-ray (EDX) spectroscopy. The FTIR result confirms the presence of phosphate (PO4-3), hydroxyl (OH)- and carbonate (CO3-2) groups in the powder. SEM displays the surface morphology whereas EDX provides calcium (Ca) to phosphorous (P) ratio in the HAP samples. The results of the EDX analysis indicate that the Ca/P ratio of HAP varies from 1.67 to 1.83. The extracted HAP material is found to be thermally stable up to 1100ÂºC.